Identification of pluriannual periodicities in series of drought indexes and its relationship with macroclimatic indicators - Vicario, Leticia del Valle (2019)
In Latin America, drought studies generally develop on climatic or hydrological approach and there are few studies available on the relationship between different kind of droughts and macroclimatic processes. The main objective of this paper was to relate the times series of droughts indexes to relevant macroclimatic indicators in Central Region of Argentina. For that, the Fourier analysis was used to identify the pluri-annual periodicities of macroclimatic indicators and representative indexes of hydrometeorological and hydrological droughts. The indexes were calculated with time series of precipitation and flow data of stations located in Carcarañá River basin. According to dominant frequencies, series with Fourier band-pass filters were filtered. Full and filtered series of indexes and indicators were compared through the correlation coefficient, for to identify and compare the time scale of the processes involved. A significant relationship in pluriannual periodicities of some droughts indexes and macroclimatic indicators was observed.